Inter- and intraspecific variation in foliar elemental concentrations in alpine plants - Feline Peters; Stefan Dullinger; Andrea Watzinger; Mathias Mayer; Karl Hülber; Norbert Helm; Kryštof Chytrý; Vanja Matijević; Paula Olías García; Nicolas Türk; Peter Hietz (Alpine Botany, 2026)
Plant species differ in their nutrient uptake, yet the relative importance of species identity versus environmental variables in shaping foliar elemental composition remains poorly understood. We collected foliar samples from ten alpine plant species across 21 plots spanning an elevational gradient of ~ 1000 m on the silicate-based soils of Schrankogel, Austria. Our aim was to disentangle the effects of species identity, site properties, and leaf traits on the concentrations of 16 elements. Foliar elemental concentrations showed a clear correlation structure, reflecting similarities in uptake mechanisms, physiological function, and stoichiometric requirements. Species identity was the dominant driver, explaining 41% of unique variance — far exceeding the contributions of site/soil properties or leaf traits. However, substantial interactions between species, site properties, and leaf traits indicate that element-environment relationships are species-specific, reflecting differences in uptake mechanisms or requirements among species. Soil temperature, soil carbon, and leaf age were the most important individual predictors across elements. Overall, the patterns suggest that while species identity predominantly drives alpine plant elemental composition, elements associated with mineral weathering (Fe, Al) and organic matter cycling (N, P) remain sensitive to environmental conditions, with implications for nutrient cycling under climate change in mountain ecosystems.

Does meter-scale snow data matter for modeling alpine plant distribution? A comparison of four data sources at two resolutions - Andreas Kollert; Kryštof Chytrý; Norbert Helm; Karl Hülber; Dietmar Moser; Johannes Wessely; Stef Lhermitte; Simon Gascoin; Andreas Mayr; Patrick Saccone; Johannes Hausharter; Michael Warscher; et al. (Ecological Modelling, 2026)

How well do SDMs calibrated at large extents predict distribution in sub-areas: A case study - Moritz Fallgatter; Stefan Dullinger; Karl Hülber; Dietmar Moser; Norbert Helm; Kryštof Chytrý; Johannes Hausharter; Johannes Wessely (Ecological Modelling, 2025)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)